Evaluating the efficiency of baited pitfall traps covered with mesh panels for sampling dung beetles - Van Bac, Bui (Journal of Forestry Science and Technology, 2024)
Baited pitfall traps represent a widely utilized method for dung beetle sampling. The effectiveness of this approach can be influenced by various factors, such as the type of bait used, trap size, and modifications to trap components. An important challenge during trapping is the inadvertent capture of non-target animals (such as: frogs, lizards, snakes, small rodents, and spiders), a concern that becomes more pronounced if endangered species are involved. To address these issues, incorporating a mesh panel into pitfall traps can help prevent unwanted intrusions. In this study, we assess the efficiency of baited pitfall traps covered with 2 cm mesh panels (BPTMP) for sampling dung beetles in tropical karst ecosystems within the Huu Lien Nature Reserve (northern Vietnam), comparing them with typical baited pitfall traps (BPT). The result revealed no significant differences in the species composition of dung beetles between the two trap types. Although the abundance of large-bodied dung beetles was significantly lower in BPTMPs compared to trap BPTs, the overall abundance and diversity of dung beetles did not significantly differ between the two trap types. Therefore, we strongly recommend adopting this sampling technique in studying on the diversity of dung beetles.